(3GdQjGVjGJ GdeGdjI (B/s - (3ehSi, TbjQj fhQjs; (3UGaj, hdjO CMeO s ((3YeGf(B: s (3OGQ GdeSjQI ddfTQ hGdJhRjY(B, s, 2011)
(3GddhZGQjJe h GdGSS h GdLPhQ, GdeYGOdGJ h GdeJhGdjGJ , GdQHG h HjGf McegG GdTQYj h GdJWQb Gdi CVQGQgG, GdaGFOI h GdaGFOI GdeQcHI , GSJgdGc GdbQhV WhjdI GdCLd HaGFOI eQcHI, Jbjje GdSfOGJs
Keywords: (3GdEbJUGO GdJMdjdjs; (3GdEbJUGO GdQjGVjs